Labor code of the Philippines with amendments : Presidential decree no. 442 ([Intramuros, Manila] : Institute of Labor and Manpower Studies, 1982)
This volume also contains related labor law and presidential issuances, particularly those concerning wages and wage supplements and overseas employment. 442: Labor Code of the Philippines. A DECREE INSTITUTING A LABOR CODE, THEREBY REVISING AND CONSOLIDATING LABOR AND SOCIAL LAWS TO AFFORD PROTECTION TO LABOR, PROMOTE EMPLOYMENT AND HUMAN RESOURCES DEVELOPMENT AND INSURE INDUSTRIAL PEACE BASED ON SOCIAL JUSTICE.
Book 1. Pre-Employment -- Book 2. Human Resources Development -- Book 3. Conditions of Pre-employment -- Book 4. Health safety and Social welfare benefits -- Book 5. Labor Relations -- Book 6. Post Employment -- Book 7. Penal provisions, prescription, transitory and Final provisions.
Philippines with amendments :, Labor
Keywords: LABOR -- LAWS AND LEGISLATIONS -- PHILIPPINES